Engineering know-who : why social connectedness matters to global design teams - Larsson, Andreas (Luleå, 2005)
The background of this thesis is the development of global, ‘virtual’, collaboration teams in the engineering domain. Distributed concurrent engineering is probably the ‘holy grail’ of current research into collaborative engineering. In this thesis, I seek to identify what some of the challenges for effective distributed collaborative engineering might be. The guiding theme of my work is the assumption that these challenges are not merely technical. Rather, I deal with the challenge of successfully merging what is required ‘socially’ with what is required technically. Methodologically, this thesis draws on an orientation to be found in Computer Supported Cooperative Work (CSCW), whereby ethnographic approaches – in-situ studies of practice – inform design work. I apply this broad perspective to the specific domain of engineering, and to the specific problem of collaboration at a distance. The thesis relies on work conducted at a number of sites. These include a major Swedish automotive company, distributed collaborative work between Luleå University of Technology, Stanford University, and the Royal Institute of Technology in Stockholm, and studies undertaken with partner companies in the Polhem Laboratory. This work has evolved towards a focus on aspects of knowledge work and expertise sharing. The contribution of the thesis is to describe and analyse the ways in which ‘Know-Who’ and related concepts are significant features of face-to-face interaction in engineering environments, and thus how they present a challenge for effective distributed collaboration. I identify the ways in which ‘ready-to-hand’ knowledge of practices, knowledge of expertise, and trust in expertise are critical to successful collaboration in engineering work, and reflect upon ways in which these issues can be better integrated into approaches to technical support for this work. Godkänd; 2005; 20060925 (cira)